Mai 68 ou l’imagination paradoxale
May 68 is a chronotype which occupies a special place in the current imaginary since it means an event that switches continually between excess and lack, where everything takes place and nothing really happens. Between sacrifice and the feast, transgression and return to the order, May 68 has something unspeakable that belongs to the ephemeral and the long duration, the epidermic surface of the history and the deep song of the Myth from which flows a complex vision of the world and a rich and paradoxical imagination.